7.7k views
3 votes
A) work out (8 x 10^-3) x (2 x 10^-4). Give your answer in standard form.

B) work out (6 x 10^2) ÷ (3 x 10^-5). Give your answer in standard form.​

User Llude
by
5.8k points

1 Answer

6 votes

Explanation:


A) \\ (8 * {10}^( - 3) ) * (2 * {10}^( - 4) ) \\ = 8 * 2 * {10}^( - 3) * {10}^( - 4) \\ = 16 * {10}^( - 3 - 4) \\ = 16 * {10}^( - 7) \\ = 1.6 * {10}^( - 6) \\ \\ B) \\ (6 * {10}^( 2) ) / (3* {10}^( - 5) ) \\ \\ = \frac{6 * {10}^( 2)}{3* {10}^( - 5)} \\ \\ = \frac{2* {10}^( 2)}{ {10}^( - 5)} \\ \\ = 2 * {10}^( 2 + 5) \\ \\ = 2 * {10}^(7) \\

User Wheleph
by
5.6k points